Teaching Russian As A Foreign Language In Pedagogical Universities - Khosiyat Nazarovna Kadirova (Euro Asian Journal Publishing, 2024)
The article discusses various approaches to the use of computer technologies in teaching RFL and methods of working with modern computer teaching aids. Various types of Internet resources, electronic dictionaries and libraries, databases, distance courses are characterized, and the process of creating a new virtual learning environment is analyzed. Particular attention is paid to the methodology of creating exercises and tasks using the Internet
Keywords: Russian as a foreign language, Internet, computer technology, virtual educational environment, computer exercises and assignments